2016
DOI: 10.1177/1078155215621150
|View full text |Cite
|
Sign up to set email alerts
|

Cardiotoxicity in targeted therapy for breast cancer: A study of the FDA adverse event reporting system (FAERS)

Abstract: Purpose Cancer chemotherapy-induced cardiotoxicity is concerning. Certain anthracyclines and targeted therapies are known to have potential for cardiotoxicity, but existing trial evidence is inadequate to understand real-world patterns of cardiotoxicity with newer targeted therapies and their common combinations with older agents. This study evaluated chemotherapy-related cardiotoxicity reports for targeted therapies and their combinations in breast cancer patients. Methods The US Food and Drug Administration … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
1
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 22 publications
(24 citation statements)
references
References 50 publications
(90 reference statements)
1
21
1
1
Order By: Relevance
“…In fact, this observation was associated with Trastuzumab. (44) Hypertension, the most extensively studied comorbidity in this patients' population, is a generally accepted risk factor and its importance was confirmed in several studies. (31) Nevertheless, the results are not uniform and there are studies that, like this study, could not demonstrate its predictive role.…”
Section: (3841)mentioning
confidence: 76%
“…In fact, this observation was associated with Trastuzumab. (44) Hypertension, the most extensively studied comorbidity in this patients' population, is a generally accepted risk factor and its importance was confirmed in several studies. (31) Nevertheless, the results are not uniform and there are studies that, like this study, could not demonstrate its predictive role.…”
Section: (3841)mentioning
confidence: 76%
“…Nonetheless, none of the targeted drugs have shown significant benefit in OS, except for a subgroup of patients receiving lenvatinib or cabozantinib (17,18). Regardless of the limited treatment effect, a high rate of adverse events was observed in patients who received targeted therapy (19,20). Immunotherapy, including immune cells and checkpoint inhibitors, may provide a new alternative option for TC with poor prognosis, as it has shown survival benefit in other oncology studies (21,22).…”
Section: Discussionmentioning
confidence: 99%
“…These directed anticancer agents are currently widely used and constitute three of the leading chemotherapy revenues in the USA, in that bevacizumab, and trastuzumab revenues in 2014/2015 in the USA alone were $3 billion, and $2.4 billion, respectively (statista.com). Despite their broad utilization in cancer treatment, FAERS database reported that between 2004 and 2010, trastuzumab had highest number of cardiotoxicity reports followed by bevacizumab (Wittayanukorn et al, 2015). …”
Section: Cardiotoxicity Of Anti-cancer Therapeuticsmentioning
confidence: 99%